Protecting Older Adults from Financial Scams: Evidence on Financial Literacy, Financial Advice, and Cognitive Ability in Indonesia - Anggita Luthfiana Safitri; Nurist Surraya Ulfa (Borong Newinera Publisher, 2026)
Indonesia has become a high-risk setting for financial scams as older adults are increasingly integrated into formal and digital financial systems. This study examined whether financial advice, self-rated cognitive abilities, and financial literacy predict financial scam susceptibility among retired older adults in Central Java, Indonesia. Using a quantitative cross-sectional survey design, data were collected from 221 retired older adults through structured interviews. Four reflective constructs were measured using six items each on a five-point Likert scale. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4. The results showed that financial literacy was the only significant predictor of lower financial scam susceptibility, while financial advice and self-rated cognitive abilities were not significant when financial literacy was included in the model. The model explained 18.5% of the variance in scam susceptibility. These findings suggest that protection against financial scams among older adults depends less on perceived mental capability or the mere availability of advice and more on practical financial knowledge that enables individuals to recognize suspicious offers, verify information, and resist pressure before compliance occurs. The study highlights the importance of scenario-based financial literacy programs, family-supported verification practices, and fraud-specific behavioral training for older adults in Indonesia.